Film Animasi Berbasis Budaya: Sebuah Peluang Bisnis Berkelanjutan - Gede Pasek Putra Adnyana Yasa; Ngurah Adhi Santosa (Jayapangus Press, 2018)
Animated films are works of art that are always in demand by the general public. Not only children, but adults also like it. The amount of public that interested in animated films has made producers compete to produce it as a business field. In the future, culture-based animation films have considerable business opportunities. This was the evident from several cultural-based animated films that attract the audience, for example Mulan's animated film about Chinese legends, Kungfu Panda about Kung Fu culture, Upin Ipin about Malaysian culture, Adit and Sopo Jarwo and Knight Kriss about Indonesian culture, and Si Uma about Balinese culture . This study aims to analyze animated films that raise cultural themes, have sustainable business opportunities. Data is taken from visual analysis, observation and in-depth interviews. Visual analysis was carried out on several animated films and articles on the internet relating to animated films that were the object of analysis. Observations and interviews were carried out on the community in order to find out their opinions regarding cultural-based animated films. This study uses a qualitative method with an interpretative qualitative approach. The theory used is the commodification theory from Faireclough. The results of the study show that some animated films that carry cultural themes are of considerable interest to the public. There are several animated films including being able to reap the highest top 10 income. Not only the culture of the local community is used as an animated film, but also outside society who want to know the culture of others. Therefore, the business opportunities for animated films that raise the theme of culture are very promising to continue to be developed in a sustainable manner.